Air battles over Hungary 1944-45 - Chazanov, Dmitrij Borisovič 1954- (Helion and Company, 2021)
"This work is dedicated for the most part to the fighting over Hungary during the course of the Debrecen (6 October - 27 October 1944) and Budapest (29 October 1944 - 13 February 1945) offensives, as well as the Balaton Defensive Operation (6 - 15 March 1945), which the Red Army carried out from autumn 1944 until the spring of 1945. The conduct of these operations preceded an attempt by the Regent of Budapest, Miklos Horthy, to pull his country out of the war. This attempt however was unsuccessful - Vice Admiral Horthy was replaced under Hitler's orders by the pro-Hitlerite henchman Szalasi, after which fierce and desperate battles broke out both on the ground and in the air. Moreover the Wehrmacht were constantly augmenting their forces, first and foremost their panzers.
Keywords: Geschichte 1944-1945; Zweiter Weltkrieg; Luftkrieg; Sowjetunion; Ungarn; World War, 1939-1945 / Campaigns / Hungary; Military campaigns; Hungary; 1939-1945